Multichannel Investigation of Interoception: Sensitivity Is Not a Generalizable Feature - Ferentzi, Eszter; Bogdány, Tamás; Szabolcs, Zsuzsanna; Csala, Barbara; Horváth, Áron; Köteles, Ferenc (Frontiers in Human Neuroscience, 2018)
Objective The term interoception refers to the perception of bodily cues. In empirical studies, it is assessed using heartbeat detection or tracking tasks, often with the implicit assumption that cardioception reflects general interoceptive ability. Studies that applied a multichannel approach measured only a limited number of modalities. In the current study, six modalities were assessed to gain a deeper understanding of the relationship between the different sensory channels of interoception. Methods For 118 university students (53% male) gastric perception (water load test), heartbeat perception (Schandry task), proprioception (elbow joint), ischemic pain (tourniquet technique), balancing ability (one leg stand), and perception of bitter taste were measured. Pair-wise correlation analysis and exploratory factor analyses (principal component analysis and maximum likelihood extraction with oblimin rotation) were then carried out with a three factor solution to investigate the underlying associations. Results Correlation analysis only revealed significant associations between variables belonging to the same sensory modality (gastric perception, pain, bitter taste). Similarly, the three factors that consistently emerged in the factor analyses represented the three aforementioned modalities. Discussion Interoceptive sensitivity assessed by using one channel only cannot be generalized. Interoceptive modalities carrying crucial information for survival are not integrated with other channels.